2013
DOI: 10.1186/1755-7682-6-41
|View full text |Cite
|
Sign up to set email alerts
|

The mirror neuron system in post-stroke rehabilitation

Abstract: Different treatments for stroke patients have been proposed; among them the mirror therapy and motion imagery lead to functional recovery by providing a cortical reorganization. Up today the basic concepts of the current literature on mirror neurons and the major findings regarding the use of mirror therapy and motor imagery as potential tools to promote reorganization and functional recovery in post-stroke patients. Bibliographic research was conducted based on publications over the past thirteen years writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 69 publications
0
28
0
9
Order By: Relevance
“…It provides visual and proprioceptive feedback of the intact arm, which may provide a substitute input for absent or reduced proprioceptive feedback from the affected arm [27]. In addition, the mirror therapy might be associated with the mirror neuron system and promote reorganization and functional recovery [25,28]. A growing number of studies have shown that the mirror therapy could be a beneficial approach for enhancing patients' motor and function after stroke [20, 21, 23-25, 29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…It provides visual and proprioceptive feedback of the intact arm, which may provide a substitute input for absent or reduced proprioceptive feedback from the affected arm [27]. In addition, the mirror therapy might be associated with the mirror neuron system and promote reorganization and functional recovery [25,28]. A growing number of studies have shown that the mirror therapy could be a beneficial approach for enhancing patients' motor and function after stroke [20, 21, 23-25, 29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Mirror therapy has also been shown to aid motor recovery and improve walking velocity and passive range of motion for ankle dorsiflexion after stroke (Broderick et al, ; Thieme et al, ). Based on visual stimulation, mirror therapy has demonstrated to activate the mirror neuron system (Carvalho et al, ) and enhance bilateral M1 excitability (Rossiter et al, ). Mirror visual feedback of the training limb overrides proprioception and increases attention of the resting limb, further enhancing activation of the untrained hemisphere (Deconinck et al, ; Touzalin‐Chretien, Ehrler, & Dufour, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mirror therapy has also been shown to aid motor recovery and improve walking velocity and passive range of motion for ankle dorsiflexion after stroke (Broderick et al, 2018;Thieme et al, 2018). Based on visual stimulation, mirror therapy has demonstrated to activate the mirror neuron system (Carvalho et al, 2013) and enhance bilateral M1 excitability (Rossiter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The idea behind it is that coupling motor imagery from the 2.1. NERVOUS SYSTEM AND THE BRAIN patient, meanwhile observing actual movement from another individual or segments of their own body, will promote the recruitment of mirror neurons and cortical reorganization that can reactivate motor neurons, resulting in the subsequent learning of new motor skills [77]. This is still a premature field, but the application of mirror therapies has shown good results when combined with other therapies showing promise in the better recovery of post-stroke patients [77], [78].…”
Section: Mirror Neuronsmentioning
confidence: 99%